Green Human Resource Management: A Review and Research Agenda*. (10th January 2012) - Renwick, Douglas W.S.; Redman, Tom; Maguire, Stuart
<x xml:space="preserve">Abstract</x> The paper makes a case for the integration of the largely separate literatures of environmental management (EM) and human resource management (HRM) research. The paper categorizes the existing literature on the basis of Ability–Motivation–Opportunity (AMO) theory, revealing the role that Green human resource management (GHRM) processes play in people‐management practice. The contributions of the paper lie in drawing together the extant literature in the area, mapping the terrain of the field, identifying some gaps in the existing literature and suggesting some potentially fruitful future research agendas. The findings of the review suggest that understanding of how GHRM practices influence employee motivation to become involved in environmental activities lags behind that of how organizations develop Green abilities and provide employees with opportunities to be involved in EM organizational efforts. Organizations are not using the full range of GHRM practices, and this may limit their effectiveness in efforts to improve EM.